2016
DOI: 10.1007/s12178-016-9315-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of the biconcave (B2) glenoid

Abstract: Glenohumeral osteoarthritis produces a wide spectrum of glenoid pathology. The B2 glenoid is defined by asymmetric posterior bone loss with the development of a biconcavity and posterior translation of the humeral head. Progressive bone loss results in increasing glenoid retroversion, which must be corrected during anatomic shoulder arthroplasty. The goals of arthroplasty should also include centering the humeral head and restoring the normal glenoid joint line. When there is minimal bone loss, this may be acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…8,9,11 The surgical treatment of shoulder osteoarthritis in this scenario includes hemiarthroplasty (HA) with or without asymmetric reaming (anterior reaming), TSA with asymmetric reaming, TSA with glenoid bone graft, TSA with augmented glenoid component, or RSA. 19,20 HA provides poor results in the context of eccentric posterior glenoid wear. 9,10 In addition, the outcomes of HA are worse compared to TSA in the presence of posterior glenoid bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,11 The surgical treatment of shoulder osteoarthritis in this scenario includes hemiarthroplasty (HA) with or without asymmetric reaming (anterior reaming), TSA with asymmetric reaming, TSA with glenoid bone graft, TSA with augmented glenoid component, or RSA. 19,20 HA provides poor results in the context of eccentric posterior glenoid wear. 9,10 In addition, the outcomes of HA are worse compared to TSA in the presence of posterior glenoid bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although some authors have advocated HA with eccentric anterior reaming, 21 23 there are concerns on joint line medialization that could worsen posterior shoulder instability. 19,20 Even in the setting of TSA, eccentric reaming alone is not recommended if glenoid retroversion is greater than 15° or the posterior bone loss is greater than 8 mm. 24 26 Correction of the glenoid retroversion with eccentric anterior reaming leads to joint line medialization, use of a smaller glenoid component, medial cortex perforation, and medial subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…The reamer was oriented so that reaming yielded a smooth concave surface with a 60-mm diameter of curvature (to match the back of the glenoid component) with the removal of the smallest possible amount of bone, without a specific attempt to normalize glenoid version. For type-B2 glenoids, the crest between the paleoglenoid 48 and the neoglenoid was removed with a burr; the glenoid reamer was then oriented equidistant from the anterior and posterior edges of the glenoid. In cases in which there was a large amount of glenoid retroversion, access for reaming was accomplished by a complete resection of osteophytes, careful retraction of the proximal part of the humerus, and positioning of the arm.…”
Section: Methodsmentioning
confidence: 99%
“…More wear and deformity secondary to osteophyte formation make pin placement more difficult. 21 In addition, there is likely a limit to the amount of correction that can be obtained by reaming the anterior, high side. Studies have suggested that reaming can make up for up to 8 mm of bone loss of the posterior glenoid and version corrected up to about 15 .…”
Section: Eccentric Reaming and Anatomic Tsamentioning
confidence: 99%